2012
DOI: 10.4103/0259-1162.108298
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the subglottic region by ultrasonography for estimation of appropriate size endotracheal tube: A clinical prospective study

Abstract: Background:Endotracheal intubation is important to carry out various surgical procedures. The estimation of endotracheal tube size is governed by narrowest diameter of the upper airway. The objective of the study was to assess the narrowest tracheal diameter by ultrasound for selection of the appropriate size endotracheal tube.Materials and Methods:After the approval of institution ethical committee and written informed consent, 112 patients aged 3 to 18 years of both genders with normal airways, scheduled for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 18 publications
5
38
0
4
Order By: Relevance
“…Gupta K and co-researchers [1] compared the size of ETT predetermined by USG and estimated by age based formula with clinically used ETT for intubation during general anaesthesia and found that there was high correlation between clinically used ETT and predetermined ETT by USG than predicted by age based formula. Their study also showed that direct measurement of the subglottic diameter by USG predicted the appropriate ETT size.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Gupta K and co-researchers [1] compared the size of ETT predetermined by USG and estimated by age based formula with clinically used ETT for intubation during general anaesthesia and found that there was high correlation between clinically used ETT and predetermined ETT by USG than predicted by age based formula. Their study also showed that direct measurement of the subglottic diameter by USG predicted the appropriate ETT size.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, if on gradual reduction of pressure a leak occurred at an inflation pressure less than 10 cm of water, the ETT was exchanged for one that was 0.5 mm larger. ETT size was considered optimal when a tracheal leak was detected at an inflation pressure between 10-20 cm of water [1,7]. The final ETT that was intubated and found optimal on the OT is considered as clinically used ETT.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations